Association of the Occurrence of Ant Species (Hymenoptera: Formicidae) with Soil Attributes, Vegetation, and Climate in the Brazilian Savanna Northeastern Region - Silva, E. F.; Cora, J. E. [UNESP]; Harada, A. Y.; Sampaio, I. B. M. (Univ Estadual Feira Santana, 2017)
Ants occur in all tropical forest strata by nesting, foraging, and interacting with plants and other residents from these habitats. Most ants build their nests in the soil. Selecting the proper soil for nesting depends on soil attributes and other factors. The question is: Which of these attributes can affect more strongly the decision for nest installation? This study aims to discover if the occurrence of some species of ants from Cerrado, in the Northeastern State of Maranhao, depends on attributes of soils and climatic factors. We found 48 species of ants, of which ten had the highest importance value. These are correlated with soil properties, litter biomass, basal area, humidity, and temperature by using the principal component analysis (PCA). The soil properties, vegetation (basal area and dry mass of litter), temperature, and humidity had an impact on the occurrence of the ten studied species of ants. Camponotus comatulus (Mackay, 2010), Ectatomma muticum (Mayr, 1870), Solenopsis substituta (Santschi, 1925), Pseudomyrmex termitarius (Smith, 1855) and Pheidole casta (Wheeler 1908) were associated with sites of arbustive vegetation, poorly and acidic chemical and physical limited (dense, high micro-pores volume) soils. Pseudomyrmex boopis (Roger, 1863), Dinoponera gigantea (Perty, 1833), Ochetomyrmex neopolitus (Fernandez, 2003) are found in fertile soils, covered by arboreal forest, while Crematogaster cf acuta, Solenopsis bruesi (Creighton, 1930) was mainly found in saturated soil, and covered with palm trees. The species of ants recorded in this study are strongly associated with soil properties, as well as vegetation parameters, air temperature, and relative humidity at soil level.
Keywords: Cerrado; soil properties; multivariate analysis; ant nest